2022
DOI: 10.3390/ijms23158658
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanism of Action of Curcumin in Experimental Models of Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) is characterized by a combination of inflammatory and demyelination processes in the spinal cord and brain. Conventional drugs generally target the autoimmune response, without any curative effect. For that reason, there is a great interest in identifying novel agents with anti-inflammatory and myelinating effects, to counter the inflammation and cell death distinctive of the disease. Methods and results: An in vitro assay showed that curcumin (Cur) at 10 µM enhanced the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In relation to melatonin, it has been evaluated in clinical assays related to cranial nerve diseases, multiple sclerosis, epilepsy, sleep disorders, spinal cord injuries, migraine, trauma brain injury, dementia, Huntington, Alzheimer and Parkinson Diseases [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. Of note, some of these diseases have also been studied in experimental models, evaluating the neuroprotective effect of these compounds mainly by their antioxidant and anti-inflammatory properties [ 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 ]. Moreover, the effects of quercetin, melatonin and curcumin have been explored in obese patients in different studies, but they have not proposed gliosis as an important comorbidity [ 2...…”
Section: Protective Role Of Antioxidants In Gliosismentioning
confidence: 99%
“…In relation to melatonin, it has been evaluated in clinical assays related to cranial nerve diseases, multiple sclerosis, epilepsy, sleep disorders, spinal cord injuries, migraine, trauma brain injury, dementia, Huntington, Alzheimer and Parkinson Diseases [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. Of note, some of these diseases have also been studied in experimental models, evaluating the neuroprotective effect of these compounds mainly by their antioxidant and anti-inflammatory properties [ 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 ]. Moreover, the effects of quercetin, melatonin and curcumin have been explored in obese patients in different studies, but they have not proposed gliosis as an important comorbidity [ 2...…”
Section: Protective Role Of Antioxidants In Gliosismentioning
confidence: 99%
“…In vitro, curcumin reduces the apoptosis of oligodendrocytes and exerts an inhibitory effect on CD4+ T-cell proliferation and differentiation, reducing the levels of secreted proinflammatory cytokines, including IL-6, IL-1β, TGF-β, TNF-α, and others. Curcumin increased serum levels of anti-inflammatory molecules such as TGF-β and IL-10 in EAE mice treated with curcumin [ 128 ]. In addition, curcumin may inhibit the inflammatory response mediated by microglia by inactivating the AXL/JAK2/STAT3 signaling pathway [ 129 ].…”
Section: Molecular Mechanisms Of Polyphenol Action On Neuroinflammati...mentioning
confidence: 99%
“…The administration of curcumin led to a reduction in the activation of TLR4 and TLR9 receptors in CD4+ and CD8+ T-cells [ 133 , 134 ]. Finally, it has been demonstrated that in the brains of cuprizone mice, curcumin treatment not only increased the activity of antioxidant enzymes, such as superoxide dismutase (SOD) and catalase (CAT), and the levels of glutathione (GSH) but decreased demyelination [ 128 ].…”
Section: Molecular Mechanisms Of Polyphenol Action On Neuroinflammati...mentioning
confidence: 99%
See 1 more Smart Citation
“…101,102 Also, curcumin is able to activate Th1/Th2/Th17 response, which helps in protecting the neuroimmune and modulate the release of inflammatory cytokines in stimulated astrocytes and declined the clinical manifestation in EAE mice by reduction of demyelination. 103 Curcumin's effects are so dosedependent, it is obviously toxic at high in vitro doses, beyond its use in cancer therapy. 104 The protective effects of curcumin, including anti-amyloid, anti-inflammatory, and antioxidant activities, could be achieved by doses at or below 1 μM.…”
Section: The Anti-inflammatory Antioxidant and Nuroprotective Effects...mentioning
confidence: 99%